Respuesta de dos híbridos de maíz (Zea mays L.), a diferentes niveles de fertilización en la zona de Babahoyo - Jara Moran, Alex Gustavo (2019)
IX. SUMMARY The work was carried out on the grounds of the community "Carolina 1" of the Cooperativa 9 de octubre, located at km 9.5 of the Babahoyo - Baba road of the Province of Los Ríos. The main objective was to evaluate the effect of nitrogen, phosphorus and potassium levels in the production of two maize hybrids. The sowing was carried out with the hybrids DK-7508 and Emblem 777 in plots of 26 m2. The treatments were distributed in a split plot design. For the evaluation of means, the Tukey test at 5% significance was used. As agronomic variables were evaluated: height of plants, height of insertion, length of ears, number of grains, weight of grain, days to flowering, days to harvest, yield per hectare, agronomic efficiency and economic analysis.The results established that the agronomic behavior of the crop is strongly influenced by the application of fertilizers. The hybrids DK-7508 and Emblem 777 fertilized with 138-69-90 kg / ha (9990 kg / ha and 9865.0 kg / ha, respectively) had the highest grain yield. In the interactions, the hybrids DK-7508 and Emblem 777 fertilized with 138-69-90 kg / ha had the best retention rate, superior to the other treatments. It should be noted that the treatment 92-23-30 kg / ha presented the lowest efficiency rate in relation to the control.